TINJAUAN YURIDIS TANGGUNG JAWAB KOMISI PEMLIHAN UMUM (KPU) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMILIHAN UMUM SERENTAK - Dara Mutiara Wani; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The General Election Commission (KPU) juridically has the responsibility oforganizing the democratic party stage commonly known as elections. Thus, the main key inthe successful implementation of elections lies in the hands of the KPU, this is regulated inLaw Number 17 of 2017 concerning General Elections. Voter participation is ofteninterpreted as an indicator of electoral success in various electoral histories in Indonesia.One of the factors of low political participation in the community is due to socializationwhich is only carried out ahead of simultaneous elections. Not only that, the KPU is still notoptimal in providing understanding and awareness for voters to participate in simultaneouselections and socialize about elections.This type of research can be classified into the type of normative legal research. Thisstudy used secondary data consisting of primary legal materials, secondary legal materials,tertiary legal materials and data collection techniques were carried out using the librarystudy method.From the results of the research and discussions carried out, there are severalconclusions obtained, namely: First, the responsibility of the KPU in increasing publicparticipation in simultaneous elections has not run optimally and there are still shortcomingsin carrying out its duties and responsibilities in accordance with applicable regulations.Second, the factors inhibiting the KPU in increasing public participation in simultaneouselections include geographical location, lack of role of political parties, community mindset,problems with the Daftar Pemilih Tetap List (DPT), obstacles when conducting socialization,limited human resources owned by the KPU, and negative public views on elections. Third,the ideal concept of KPU in increasing community participation in the 2024 simultaneousgeneral elections consists of various efforts that can be done including, carrying outsocialization of Goes to Campus and Goes to School, socialization with assisted citizens,forming democratic cadres and embracing community and youth organizations, the use ofsocial media and mass media, dissemination of information through props, socialization ofmobile cars, methods of socialization with electiontainment, democracy ambassadorprograms, and working with educational agencies and work environments to disseminate A5forms. The author's suggestion is that there is a need to strengthen the KPU institution as awhole by creating a new legal rule or a separate KPU regulation regarding the KPU'sresponsibility in increasing community participation, so that later related to the functions andauthorities of the KPU will be stronger, especially in increasing public awareness toparticipate in simultaneous elections, so that later a legal certainty and rules are guaranteedby individuals and the community in political participation.Keywords: KPU, Community Participation, Simultaneous General Elections